2018
DOI: 10.1097/scs.0000000000004939
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Vertical Triangular Spreader Graft Technique for Reconstruction of Middle Vault and Internal Nasal Valve Angle

Abstract: Background: Rhinoplasty is a surgical procedure to smooth out the nasal deformities and to fix nasal breathing problems. Spreader grafts and flaps are used to prevent some complications such as middle vault collapse, narrowing the internal nasal valve and inverted V deformity. To obtain more stable middle vault, spreader grafts and flaps could be used together. Many researchers have tried different graft and flap techniques to reach more successful aesthetic and functional results. In this research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(24 citation statements)
references
References 11 publications
1
23
0
Order By: Relevance
“…Hussein et al (14) presented an increase of the angle postoperatively without mentioning the level of statistical significance. Kocak et al (22) presented a statistically significant increase in the nasal valve angle postoperatively in all three study groups (p=0.00). Although, the highest postoperative improvement was observed in the SF group with triangular SG (p=0.001).…”
Section: Endoscopic Imagesmentioning
confidence: 79%
See 4 more Smart Citations
“…Hussein et al (14) presented an increase of the angle postoperatively without mentioning the level of statistical significance. Kocak et al (22) presented a statistically significant increase in the nasal valve angle postoperatively in all three study groups (p=0.00). Although, the highest postoperative improvement was observed in the SF group with triangular SG (p=0.001).…”
Section: Endoscopic Imagesmentioning
confidence: 79%
“…Particularly, Yoo et al (18) presented a significant BFI in the group with nasal obstruction (p<0.001). In the Κocak et al study (22) , a significant reduction in the NOSE score was observed in the SF group and in the SF group with triangular SG (p=0.05). There was no significant postoperative difference between the study's groups (p=0.695).…”
Section: Nose Scorementioning
confidence: 82%
See 3 more Smart Citations